PARTISIPASI ANGGOTA KELOMPOK USAHA PENGOLAHAN MANISAN RUMPUT LAUT DI POKLAHSAR “SWAKARYA BERSAMA” KABUPATEN PENAJAM PASER UTARA - Yurida Normadayani; Eko Sugiharto; Indrati Kusumaningrum (2339-1324, 2017)
The purpose of this research was to determine the factors correlation of internal, external, and the level of participation of sweets seaweed processing group members in Poklahsar Swakarya Bersama, Penajam Paser Utara Regency. Census method was used in this research with ten respondents. The rank spearman correlation was applied to analysis the correlation of internal factor and external factor on the participation level.The analysis showed that internal factors; age was closely related to the provision of information, business experience was closely related to organizing activities, business experience was very closely related to the attitude of cooperation and provision of information. External factors; income was closely related to the attitude of cooperation and very closely related to the organizing activities, seaweed production was closely related to the organizing activities. The participation level; sweets seaweed processing group members in Poklahsar Swakarya Bersama showed high participation level.